Efficacy of Topical Dapsone 5% Gel for the Treatment of Erythematotelangiectatic Rosacea: New Treatment Option with Old Drug - Şule Gökşin; Işıl Göğem İmren; Nida Kaçar (Mattioli1885, 2024)
Introduction: Many topical drugs are used in the treatment of erythematotelangiectatic rosacea (ETR). However, dapsone 5% gel has never been used in ETR to date. Objectives: To evaluate the efficacy of dapsone 5% gel as a new treatment option for ETR. Methods: Thirty-five patients with ETR were included in the study. Diagnosis was made with National Rosacea Society criteria. Dapsone 5% gel was used topically twice a day for 12 weeks. Investigator Global Assessment (IGA) 4-point scale ( 0 → Clean, 1 → mild, 2 → moderate, 3 → severe, 4 → very severe), Visual Analogue Scale (VAS) and Dermatology Life Quality Index (DLQI) were used for evaluation (at baseline, 2nd, 6th, and 12th weeks). Results: IGA scores among baseline (2 → 62.9%, 3 → 34.3%, 4 → 2.9%) and 2nd (1 → 14.3%, 2 → 77,1%, 3 → 8.6%), 6th (1 → 45,7%, 2 → 54.3%) and 12th weeks (1 → 62.9%, 2 → 37.1%) were found to be statistically significant (P < 0.001). Median VAS scores among baseline (median = 7 [5-9]) and 2nd (median=5 [3-8]), 6th (median=5 [3-6]) and 12th weeks (median = 4 [2-6]) were statistically significant (P < 0.001). Median DLQI scores among baseline (median = 8 [6-14]) and 2nd (median = 5 [3-11]), 6th (median = 5 [3-11]) and 12th weeks (median = 4 [2-9]) were statistically significant (p<0.001). Concurrent systemic disease was a risk factor for poor treatment response (P = 0.034). Mild irritation was observed in 3 patients (8.5%) during treatment. Conclusions: Dapsone 5% gel was effective and well tolerated in ETR treatment.